The Effectiveness of Online Learning During the Covid-19 Pandemic for Students - Hikmah Rahmatul Laili; Mochamad Widjanarko; Erik Aditia Ismaya (Universitas Islam Sultan Agung, 2022)
The purpose of this study was to reveal the effectiveness of online learning during the COVID-19 pandemic. The method used is a descriptive qualitative case study with a sample of teachers and students at SD Negeri Kendalagung, Kragan, Rembang. This study uses primary data and secondary data. To obtain primary data, conducted interviews and observations of respondents to the object of research. While secondary data obtained from literacy literature, books, journals and previous research results. The results show that to prevent the spread and transmission of COVID-19, online learning must be implemented. However, due to limited human resources and limited availability of facilities and infrastructure, online learning at SD Negeri Kendalagung, Kragan, Rembang has not been effective enough. Teachers also have difficulty measuring students' abilities, because the results of online work carried out by students include intervention and intervention from their respective families.